(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the factors influencing the formation of moisture pressure in gypsiferous gray soils located in the Polvontash foothills of Southern Fergana. The aim of the study is to provide a comprehensive assessment of the effects of climate and gypsum content on soil moisture pressure. Using V.A. Kovda’s equation, the values of the moisture coefficient (Nk) and relative humidity (Rh) were calculated. Depending on the gypsum content, the moisture pressure (pF) was determined.